Production of normalweight concrete through the use of circulating fluidized bed (CFB) bottom ash - Caluscusin, Bien Marisse V.; Guillermo, Michelle S.
The research study investigated the effects of partial and full replacement of sand with CFB bottom ash in producing normal weight concrete. A total of 81 concrete samples were prepared with three different percentage mix for fine aggregates (100% sand control, 100% CFB bottom ash, and a mix of 50% sieved bottom ash and 50% sand) and with three different W/C ratios (0.50, 0.60, 0.70) per percentage mix. The samples were moist cured for 7, 14, and 28 days and tested with Rebound Hammer Test, Ultrasonic Pulse Velocity Test, and Compressive Strength Test. The results showed that the compressive strength of 100% CFB BA is lower as compared to the control concrete, while the 50% mix is comparable to that of the control concrete. The strength of the 50% mix is higher in the lowest W/C ratio (0.50) as compared to the strength of the control concrete.